Combinative phytochemical compositions and antimicrobial activities of Xylopia aethiopica and Sida acuta extracts - Reuben Essel Arhin; Elorm Adri-Walters; Henry Kwadwo Hackman; Paa Kwesi Gordon; Mark Addo Appenteng; Andrew Gordon (German Journal of Pharmaceuticals and Biomaterials, 2025)
Xylopia aethiopica (Dunal) A. Rich. and Sida acuta Burm.f. are widely recognized for their traditional medicinal properties in treating various ailments. This study seeks to uncover the phytochemical composition and antimicrobial potential of combined extracts from these two valuable plant species. We prepared solvent extracts using aqueous, 70% ethanol, absolute ethanol, and methanol from the fruits and leaves of Xylopia aethiopica, along with the leaves of Sida acuta. These extracts were then combined into four new formulations: combined aqueous (CoA), combined absolute ethanol (CoE), combined 70% ethanol (CoE70), and combined methanol (CoM). We meticulously analyzed the phytochemical compositions of these formulations. To gauge their antimicrobial activity, we examined the susceptibility of various control strains to different concentrations of the extracts through the agar well diffusion method. The minimum inhibitory concentration (MIC) was determined for the most effective combined extracts. Notably, flavonoids were discovered solely in CoA, whereas cyanogenic glycosides were present only in CoM. At a concentration of 200 mg/ml, the extract from the leaves of Xylopia aethiopica (AXL) exhibited the strongest inhibitory effect on Staphylococcus aureus ATCC 25923 (17.67 ± 0.47 mm). In comparison, CoE70 yielded significant results against Staphylococcus saprophyticus ATCC 15305 (14.00 ± 0.82 mm). AXL also showed impressive inhibition of Salmonella typhi ATCC 19430 (18.67 ± 0.47 mm) and Escherichia coli ATCC 25922 (15.00 ± 0.52 mm). The observed MICs ranged from 25 mg/ml to 3.13 mg/ml. Except for the aqueous extract of Xylopia aethiopica leaves, the combined extracts from Xylopia aethiopica and Sida acuta, produced through various extraction methods, exhibited distinct phytochemical profiles and demonstrated significantly greater antimicrobial activity than their individual counterparts. These compelling findings underscore the potential of these plants in developing more effective antimicrobial treatments.